Large Mammal Diversity in Nensebo Forest, Southern Ethiopia - Zerihun Girma; Zerubabel Worku (International Journal of Zoology)
There is a lack of information on mammalian faunal resources of remote forests in Ethiopia; as a result, the findings of the research on large wild mammals at Nensebo forest is one of the steps in a continuing effort to document and describe the diversity and distribution of Ethiopian mammals in remote and less accessible forests. The survey was conducted to assess the species composition and relative abundance of large mammals. Two standardized survey techniques, direct (sighting/hearing) and indirect (scat/footprint), were employed using systematically established transect lines and field plots in two dominant habitat types (modified moist Afromontane forest and intact moist Afromontane natural forest) of the study area. A total of 16 species were recorded including two endemic mammals, namely, Tragelaphus buxtoni and Tragelaphus scriptus meneliki. Abundance of species among different habitat types was not significantly different (χ2 = 0.125, df = 1, p>0.05), and Colobus guereza was the most abundant species. In contrast, Felis serval, Panthera leo, and Tragelaphus buxtoni were the least abundant species. The highest diversity index was recorded in the natural forest habitat (H′ = 2.188), and the modified forest had the lowest diversity index (H′ = 1.373). There is an urgent need to minimize threats and mitigate impacts.